2020
DOI: 10.48550/arxiv.2006.09551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-dependent properties of interacting active matter: dynamical behavior of one-dimensional systems of self-propelled particles

Lorenzo Caprini,
Umberto Marini Bettolo Marconi

Abstract: We study an interacting high-density one-dimensional system of self-propelled particles described by the Active Ornstein-Uhlenbeck particle (AOUP) model where, even in the absence of alignment interactions, velocity and energy domains spontaneously form in analogy with those already observed in two dimensions. Such domains are regions where the individual velocities are spatially correlated as a result of the interplay between self-propulsion and interactions. Their typical size is controlled by a characterist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(88 reference statements)
1
3
0
Order By: Relevance
“…As already reported in [16,35,57], the study of the velocity dynamics reveals the existence of hidden collective behavior of self-propelled particles at high density in the regime of large persistence times. Nevertheless, many single-particle properties, such as the velocity distribution and its moments, have not been yet explored.…”
Section: The Velocity Dynamicssupporting
confidence: 68%
See 1 more Smart Citation
“…As already reported in [16,35,57], the study of the velocity dynamics reveals the existence of hidden collective behavior of self-propelled particles at high density in the regime of large persistence times. Nevertheless, many single-particle properties, such as the velocity distribution and its moments, have not been yet explored.…”
Section: The Velocity Dynamicssupporting
confidence: 68%
“…In what follows, we develop an exact, analytical prediction valid in active the solid-state for the kinetic temperature which will explain the scaling with τ numerically observed shedding light also on the role of the other parameters. Indeed, the periodicity of the almost-solid structure and, in particular, its hexagonal order suggests switching in the Fourier space to perform calculations [35,57]. As reported in Appendix A, the velocity correlation in the Fourier space reads:…”
Section: The Kinetic Temperaturementioning
confidence: 99%
“…Starting from the AOUP, several predictions or approximations for the probability distribution [42,46,47], pressures [48,49] and surface currents near boundaries [39,48] have been derived. More recently, AOUP has been employed to derive the analytical expression for the spatial correlation of the velocity spontaneously appearing in active hexatic and solid phases [50,51].…”
Section: Modelmentioning
confidence: 99%
“…One-dimensional (1D) models are currently a subject of increasing interest. [10][11][12] In many cases, such systems produce, at least approximately, a purely exponential CSD, as shown across models of run-and-tumble bacteria, active Brownian particles, and active Ornstein-Uhlenbeck particles, both on-lattice and offlattice. 2,13 For a simple on-lattice model, it has been demonstrated that no high-density transition exists, 14 but other lattice models do phase separate more conventionally, e.g.…”
Section: Introductionmentioning
confidence: 99%